1988
DOI: 10.2135/cropsci1988.0011183x002800050012x
|View full text |Cite
|
Sign up to set email alerts
|

Forage Quality Characterization of a Chemically Induced Brown‐Midrib Mutant in Pearl Millet

Abstract: Based on the negative relationship between lignin and digestibility, one of the most effective means of increasing forage digestibility is by reducing lignin content. Our objective was to chemically induce a brown‐midrib (bmr) mutation in pearl millet, Pennisetum americanum (L.) Leeke, and evaluate the resulting mutants for lignin content and similarity to existing bmr mutants in other species. Seeds from two inbred pearl millet lines derived from Tift 23D2B1/2 ✕ PI 185642 were treated with either ethyl methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 0 publications
5
36
0
1
Order By: Relevance
“…In contrast to our results, Cherney et al (1990) reported lower NDF and ADF in the second than in the first harvest for bmr, but not for normal forage millet. Our NDF and ADF values for bmr forage millet are in agreement with those reported by Cherney et al (1988), however, our ADL values were at least 50% lower than those reported by the same authors.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…In contrast to our results, Cherney et al (1990) reported lower NDF and ADF in the second than in the first harvest for bmr, but not for normal forage millet. Our NDF and ADF values for bmr forage millet are in agreement with those reported by Cherney et al (1988), however, our ADL values were at least 50% lower than those reported by the same authors.…”
supporting
confidence: 93%
“…However, ADF was similar for both types of forage millet. Our results are consistent with other studies that showed lower NDF and ADL for bmr millet, sorghum and corn compared with their normal counterparts (Fritz et al 1981;Cherney et al 1988;Cherney et al 1990). Harvest had no effect on NDF, ADF, and ADL.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…For example, the commonly utilized brown midrib mutants (bmr) in forage maize and sorghum are mutations in genes for enzymes of the lignin biosynthesis pathway resulting in plants with reduced lignin and greater digestibility [1,2,6,8,13,14,19,20,33,36,38,47,75,105]. This suggests that accessibility of cellulose and hemicellulose by rumen microorganisms has been improved by lowering or changing the types and amounts of lignin present in cell walls.…”
Section: Introductionmentioning
confidence: 99%